RE-ORGANISING THE ACTIVE CITIZEN FORCE - Heitman, H.R. (Scientia Militaria - South African Journal of Military Studies, 2012)
Increasing numbers of Citizen Force personnel are completing their period of service and being discharged into the limbo of a general reserve. This seems a sad waste of trained personnel. A possible system whereby more efficient utilisation of such personnel could be achieved is outlined below: